33: Adrenal Suppression in the Pediatric Population in Canada. Issue 6 (1st June 2014) - Goldbloom, EB; Mokashi, A; Cummings, E; Huynh, H; Benseler, S; Watson, W; Abish, S; Ahmet, A
Abstract: BACKGROUND: Glucocorticoid (GC) therapy is effective for the treatment of many paediatric disorders. Hypothalamic-pituitary-adrenal axis suppression ('adrenal suppression' (AS)) is a proven but under-recognized side effect of GC use. The incidence of AS has not been established. AS may go undetected until a physiologic stress precipitates an adrenal crisis. OBJECTIVES: To estimate the national incidence of paediatric adrenal crisis and symptomatic adrenal insufficiency due to AS in association with GC treatment, diagnosed by Canadian Paediatricians. To describe the clinical features of AS at diagnosis and to document burden of illness. To identify characteristics of children with symptomatic AS. To generate awareness among paediatricians of the frequency of AS and associated morbidity in children on GC therapy. DESIGN/METHODS: Through the established methodology of the CPSP, >2500 paediatricians and paediatric subspecialists were actively surveyed monthly for two years to report new cases of symptomatic AS. RESULTS: Forty-four cases of symptomatic AS were confirmed. The estimated minimal annual incidence of symptomatic AS is 0.34 per 100, 000 children aged 0 to 18 years (95% CI 0.25 to 0.45). Adrenal crisis occurred in six cases (14%). The most common presentations were growth failure (36%), non-specific symptoms (25%) and both growth failure and non-specific symptoms (14%). The predominant form of GC treatment in most cases was inhaled corticosteroids (ICS). Thirty-six children (82%) received ICS alone or in combination with other GC forms. The most commonly reported ICS was fluticasone (11 of 12 of those who received ICS only; 20 of 24 of those who received ICS in combination with other GC forms). Of the 11 children who received fluticasone only, doses were 500 mcg/day (n=7) or greater (n=4). Eight children (18%) received primarily systemic GCs. CONCLUSIONS: The minimal estimated incidence reported in our study is for the entire paediatric population and would be much higher in the at-risk group (ie, children treated with GCs). The lack of consistent, specific signs and symptoms for AS indicates that many cases may not be recognized without proactive screening. The high frequency of growth failure and/or non-specific symptoms at presentation underlines the importance of close monitoring of growth and potential symptoms associated with AS. The six cases of adrenal crisis demonstrate the potential morbidity associated with this condition. Many children received high but commonly prescribed doses of ICS. To reduce the risk of AS, physicians must be aware of the risk of AS, revisit GC doses frequently to ensure that patients are being treated with the lowest effective dose, and consider the cumulative GC dose. Further studies are needed to assess screening methods and to further evaluate risk factors and duration of suppression.